Comparison of perceived and measured accessibility between different age groups and travel modes at Greenwood Station, Perth, Australia - Ryan, M.; Lin, T.; Xia, Jianhong (Cecilia); Robinson, Todd (Editorial Board EJTIR, 2016)
Although there has been a significant focus on evaluating accessibility to facilities, the differences between age groups and/or mode of access to train stations is less clear. This paper compares perceived and measured accessibility to train stations among three age groups: young adults (18-24), middle aged adults (25-59) and elderly adults (60+) and three travel modes, Park and Ride (PnR), Bus and Ride (BnR) and Walk and Ride (WnR). The study focuses on the Greenwood railway station, Perth, Australia. Measured accessibility was lower than perceived accessibility for all three age groups. Both perceived and measured accessibility to train stations were lower for the elderly than the other groups. The catchment area of elderly PnR users was also the smallest. Middle aged adults evaluated accessibility (perceived) by WnR the highest. Young adults were found to have a larger PnR catchment area than other groups. Inadequate accessibility to Greenwood Station for different age groups and by different travel modes were identified, which can be used as a decision-making aid by practitioners and station managers for improving accessibility for these cohorts. The techniques used are directly transferable to the study of other stations.